2021
DOI: 10.1016/j.tcr.2021.100514
|View full text |Cite
|
Sign up to set email alerts
|

Occult traumatic impaled foreign body, a challenging diagnosis of severe chronic lower extremity radicular pain

Abstract: The investigation of embedded soft tissue foreign bodies relies heavily on radiological imaging. The prompt identification of these objects is critical as retained foreign bodies may lead to serious infection or chronic debilitating pain depending on anatomical location. In this report, we present a case of a radiographically occult traumatically implanted foreign body in a 15-year-old female after a high-speed motor vehicle accident. Initial computed tomography (CT) scan was unremarkable and exploration under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…CT scan findings were key in the diagnostic procedure in our case. Nevertheless, some types of plastic have similar attenuation levels to soft tissues, making them undetectable via CT scan when implanted in muscular tissues, for example [ 1 , 6 ]. In such cases, MRI can be superior to CT scan for detecting foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT scan findings were key in the diagnostic procedure in our case. Nevertheless, some types of plastic have similar attenuation levels to soft tissues, making them undetectable via CT scan when implanted in muscular tissues, for example [ 1 , 6 ]. In such cases, MRI can be superior to CT scan for detecting foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, MRI can be superior to CT scan for detecting foreign bodies. As an illustration, Kartiko M et al recently reported a case in which a 10-cm plastic foreign body lodging in the deep soft tissues of the pelvis was overlooked on a CT scan and was not identified until an MRI was performed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation